Obraz jako aktor społeczny w sieci. Treści przekazywane w obrębie mikroblogów na przykładzie serwisu soup.io - Szubstarska, Magdalena (Człowiek i Społeczeństwo, 2012)
Images: Actors in the Network examines the properties of an image floating around the Internet: the ability of connecting people without usage of words, bonding them because of the mutual feelings they have about the reality outside. Images that are reposted between the users of digital forms such as tumblelogs or microblogs (the article uses soup.io for the case study) cover the needs, fears and aspirations of not only ordinary web-users, but also the users of the contemporary culture and economic system. An image is no longer a passive, visual piece – it acts by joining, addressing and portraying the desires, thoughts of the users. This phenomenon can be connected with Bruno Latour’s Actor-Network Theory, and with the ideas of W.J.T. Mitchell about the active images. The example of soup.io shows how easy it is to bond people through sharing particular images, but also how certain tools of popular culture can be used to create something new. Although it seems as soup.io users are not interested in connecting with anyone but themselves, their microblog is the message to the outside, it is their collage portrait that makes them visible to the others. Image is then not only the tool of connection, but also the tool of representation. What is important, most of the images that can be found on soup.io are anonymous – which means that they no longer belong to a certain person, but become independent and free to act.